Integrating CA4PRS V.3 road widening schedule module into US highway early constructability process: California SR-91 corridor improvement program case study - Lee, Eul-Bum; Alleman, Douglas; Thomas, David; Kim, Chang-Mo (Transport, 2020)
Performing Constructability Review Processes (CRPs) during the highway design development has been found to save transportation agencies twice their input costs. However, existing literature has identified three areas of CRP improvement: reduction of required agency resources, incorporation of Road User Cost (RUC) scheduling constraints, and integration of assessment visualizations. The authors propose to fill this gap by integrating the Construction Analysis for Pavement Rehabilitation Strategies (CA4PRS) v.3 software into the CRP. This module provides agencies with road widening project schedule capabilities, which enhances CRPs by providing accurate RUC-constrained critical path schedules using minimal resources. The module was developed through interviews with subject matter experts from six public and two private California transportation organizations. Said experts also tested the CA4PRS v.3 alpha and beta pre-release versions using data collected from eight Caltrans road widening projects. The potential value-adding of integrating the CA4PRS v.3 software with existing CRPs has been tested through its application on the California State Road 91 (SR-91) Corridor Improvement Program (CIP), resulting in 24-months of construction acceleration. The findings and presentation of the schedule model within this paper provide practitioners an accurate and resource-efficient tool to estimate the schedule impacts of road widening constructability options.